What's cooking?: participatory and market approaches to stove development in Nigeria and Kenya - Sesan, Temilade Adeyinka (2011)
Improved stoves have been promoted in the global South by international organisations from the North since the 1970s for a variety of reasons including mitigation of health and environmental hazards related to the widespread use of solid biomass for cooking. However, uptake of these stoves by poor households in the South remains low, bearing negatively on efforts to alleviate energy poverty and achieve the Millennium Development Goals (MDGs). This thesis examines the framing and impact of participatory and market-based approaches to stove development and dissemination which have been widely promoted since the mid-1980s to address the failures of the predominantly expert-led, subsidy-based models favoured in the early years. Specifically, I investigate and compare two Northern-led stove projects, one established by Project Gaia in Nigeria, where stove development efforts targeted at addressing energy poverty have been limited, and the second by Practical Action in Kenya, where such efforts are more visible.